Sosialisasi Manfaat dan Dampak Kecerdasan Buatan bagi Guru dan Pengurus Yayasan Mizan Amanah Asembaris, Jakarta Selatan - Shedriko Shedriko; Muhammad Firdaus (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Rapid advancements in technology and information, coupled with increasing anytime, anywhere online access, are transforming how people approach learning and work. Artificial Intelligence (AI) is driving innovation, new ideas, and efficiency across nearly every industrial sector. We conducted this Community Service (People Service Activity) activity to enhance the learning of teachers and foundation administrators at Mizan Amanah Asembaris, Tebet by introducing the benefits and risks associated with AI in education. We employed observation, interviews, and hands-on practice to gather information and provide guidance on the proposed solutions. This approach ensures that the information can be effectively applied and disseminated within the foundation. The program included a presentation on the potential and challenges of AI, followed by an open discussion and a brief practical session on basic tools for daily use, enabling participants to integrate these tools into their work. Ultimately, we hope they will share this knowledge with the children at the orphanage, ensuring they receive practical and applicable information.